Regulation of luteinizing hormone-releasing hormone receptor binding by heterologous and autologous receptor-stimulated tyrosine phosphorylation. - Liebow, C (1991)
Pancreatic cancers overexpress tyrosine kinase and luteinizing hormone-releasing hormone (LH-RH) receptor (LH-RHR)-mediated tyrosine phosphatase. LH-RHR is a 60-kDa protein. One of the substrates of epidermal growth factor (EGF)-stimulated tyrosine kinase activity and LH-RH- and somatostatin-stimulated tyrosine phosphatase activity is also a 60-kDa protein. This suggests the possibility that LH-RHR regulation by tyrosine phosphatase and tyrosine kinase is mediated by (de)phosphorylation of existing LH-RHR. To test this hypothesis, membranes of MIA PaCa-2 cells, a human dedifferentiated pancreatic cancer cell line, were incubated without hormone (control) or with 0.1 microM EGF or somatostatin analogue RC-160 for 1 hr at 4 degrees C to phosphorylate the 60-kDa protein. Competition binding experiments with I125-labeled [D-Trp6]LH-RH by displacement with a nonradioactive ligand showed that the LH-RH binding in 69% of the points was increased by EGF and 85% was decreased by RC-160 compared with controls (n = 61; both significant, P less than 0.001). The specific binding was altered, increasing 50-150% after preincubation with EGF and decreasing 60-70% after RC-160. No change was seen in the binding affinity constant after pretreatment with EGF or RC-160. This shows that phosphorylation regulates binding of LH-RH and may explain the up-regulation by EGF and down-regulation by RC-160 and by LH-RH of the LH-RH response.